Ecofriendly Antimicrobial Dyeing for Cotton Fabric Using Natural Extract of Marigold (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The main drawback with microorganism's development on fabrics is associated with the maintenance of hygiene and fabric deterioration. In this present investigation a trial has been made to produce an attractive and vibrant textile with eco-friendly antimicrobial dyeing by marigold, a natural resource. Tagetes erecta universally recognized as Marigold is a remarkable source of carotenoids and lutein, grown as a lawn plant. Now a day, lutein is exploding into an indubitably predominant active fitting, employed as an element of the Drugs, Nutrients and Textile Industry. The prospective application of marigold as a characteristic of antimicrobial activity has not been accustomed fully. It is due to the lack of knowledge about its ability and resemblance in material manner. In this work, we have concentrated on the analysis, which was led to deliberate the use of distillate isolate of marigold as an antimicrobial. The antimicrobial competence of the extract was evaluated by coloring on cotton textiles. Testing of the dye ability, its wash quickness and light fastness was done. Educations have validated that antimicrobial coatings have not affected by laundering and shown enhanced colouring effect comprising of fastness to washing, perspiration and rubbing than conservatively dyed textiles. It revealed that the essence of Marigold flower is habitually employed for cotton fabrics as an antimicrobial finish. The samples show very encouraging ends up in terms of antimicrobial resistivity.